I wonder why spiders spin webs: and other questions about creepy-crawlies - O'Neill, Amanda (Kingfisher London, 2011)
"This highly popular and long-running series has been revamped for a new generation of readers, with a clean, crisp redesign and colourful covers. The series explores questions that young readers ask about the world around them in an unrivalled child-friendly style. The conversational format is perfect for delivering solid information in a natural, amusing and imaginative way. Designed to amuse and intrigue the young reader, this book combines cartoons with facts and simple analogies to provide an introduction to the world of creepy-crawlies asking questions such as: which beetle fires a spray gun?; can spiders kill people?; and, which insect tastes with its toes?" (publisher)